1997
DOI: 10.1084/jem.185.3.541
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Expression of Major Histocompatibility Complex (MHC) Class II Molecules Demonstrates that Dendritic Cells Can Induce Negative but Not Positive Selection of Thymocytes In Vivo

Abstract: It is well established that lymphoid dendritic cells (DC) play an important role in the immune system. Beside their role as potent inducers of primary T cell responses, DC seem to play a crucial part as major histocompatibility complex (MHC) class II+ “interdigitating cells” in the thymus during thymocyte development. Thymic DC have been implicated in tolerance induction and also by some authors in inducing major histocompatibility complex restriction of thymocytes. Most of our knowledge about thymic DC was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
289
2
5

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 403 publications
(312 citation statements)
references
References 44 publications
16
289
2
5
Order By: Relevance
“…However, genes under control of the DC-specific CD11c promoter have been demonstrated and generally accepted to specifically express in DCs in vivo. 16,26 Our results indirectly indicates that DCs can be transfected by CD11c-Bcl-xl DNA (unpublished observations), and subsequently prolong T-cell stimulation in vivo ( Figure 2). Enhanced immunity by increased DC survival was reported in 'survival gene' Bcl-2 transgenic mice.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…However, genes under control of the DC-specific CD11c promoter have been demonstrated and generally accepted to specifically express in DCs in vivo. 16,26 Our results indirectly indicates that DCs can be transfected by CD11c-Bcl-xl DNA (unpublished observations), and subsequently prolong T-cell stimulation in vivo ( Figure 2). Enhanced immunity by increased DC survival was reported in 'survival gene' Bcl-2 transgenic mice.…”
Section: Discussionmentioning
confidence: 58%
“…Hsp70 was generated by cloning hsp70 including stop codon into pcDNA 3.1(+) vector at the unique sites of NheI and NotI using primers: 5' CTAGCTAGCATGGCCAAA GCCGCGGCAGTC and P2. Human antiapoptotic gene Bcl-xl 54 or EGFP was cloned into the CD11c-pDOI-5 vector 26 at the unique site of EcoR I using primers: Bcl-xl: 5 0 CGGAATTCACCATGTCTCAGAGCAACCGG and 5 0 CGGAATTCTCATTTCCGACTGAAGAG; EGFP: 5 0 CGG AATTCACCATGGTGAGCAAGGGCGAG and 5 0 CGGA ATTCTTACTTGTACAGCTCGTCCAT. All plasmids were confirmed by sequencing.…”
Section: Dna Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed we found that DCs showed an enhanced receptormediated binding and internalization of phage particles expressing the anti-DEC-205 scFv. However, DCs may play a dual role either inducing adaptive immune response or maintaining tolerance [13,22,23]. In particular, targeting of DEC-205 is usually not associated with the induction of antigen-specific T cells and thus in previous works additional DC activation/ maturation compounds needed to be given as well [6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…DC are now implicated in the regulation of the responses they initiate and in the maintenance of tolerance to self components [1,2]. DC are involved in both central tolerance in the thymus [3,4] and in peripheral tolerance of self-reactive T cells that have escaped intra-thymic deletion [2,[5][6][7]. The activation or 'maturation' state of the DC is believed to determine the balance between tolerance and immunity.…”
Section: Introductionmentioning
confidence: 99%